Ultrastructure of early mineral deposition during hyaline layer formation in rat molars - Tomazela-Herndl, S. A.; Arana-Chavez, V. E. (Elsevier B.V., 2001)
There is no consensus on whether the first mineralized layer, the hyaline layer, that is juxtaposed to root dentine is a variety of dentine or cementum or even a tissue of epithelial origin. Some suggest that there is no intermediate tissue between the acellular extrinsic fibre cementum (AEFC) and the root dentine. Here, to study hyaline layer formation and mineralization we examined by transmission electron microscopy the early stages of root development in upper molars from 10 to 13 day old Wistar rats. In addition to conventionally processed material, undemineralized and unstained sections were examined, which showed the deposition of fine mineral crystals in contact with the mineralized surface of root dentine. Early mineralization of the hyaline layer occurred in the region of the inner basement membrane, which persisted between the inner cellular layer of Hertwig's epithelial root sheath and the outer mineralized root dentine. When the root sheath began its fragment, collagen fibrils From the developing periodontal ligament began to insert into the mineralising hyaline layer, which was 0.5-0.8 mum wide. As the fragmentation of the root sheath HERS increased, more collagen fibrils appeared intermingled with the mineralising hyaline layer. In more advanced stages, when the hyaline layer had become fully mineralized and the formation of the AEFC began, the hyaline layer could no longer be identified. Thus, the hyaline layer is clearly discernible at early stages of periodontal development. Subsequently, it is masked by intermingling of cementum and dentine and therefore it is not possible to detect it in the formed roots of rat molars. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: hyaline layer; intermediate cementum; periodontal development; cementum; mineralization; ultrastructure